עדויות מהלשכה הקדושה: לקראת היסטוריה של המאגיה היהודית באיטליה בעת החדשה - בלושי אלסיה (מחשבת ישראל, 2025)
In this article, I propose a new methodology for reconstructing Jewish culture and Jewish-Christian relations in early modern Italy based on the combined analysis of Jewish magical sources and inquisitorial records and materials. I do so by focusing on a medallion engraved with Hebrew inscriptions and the effigy of Christ, which was confiscated by the Holy Office in Parma in 1713 and is today preserved among the holdings of the Archive of the Dicastery for the Doctrine of the Faith (ADDF) in the Vatican. When considered in relation to other Hebrew medallions of a similar nature that have been subjected to analysis within the context of Jewish magical tradition, this remarkable object serves to illustrate the potential for inquisitorial material and studies on the Inquisition(s) to facilitate research on Jewish magic, and vice versa. Furthermore, it demonstrates how the exchange of ideas between these two academic fields may contribute to a deeper comprehension of Jewish culture in Renaissance and Baroque Italy.